The bird way : a new look at how birds talk, work, play, parent, and think - Ackerman, Jennifer, 1959- (New York : Penguin Press, 2020)
Ackerman contends that recent research on how birds communicate, work, play, parent, and think reveals that the creatures are remarkably intelligent. Ackerman supports her thesis with descriptions of the behavior with a variety of birds from across the world. She further makes the case that bird intelligence shows that humankind is not alone in using language and tools or constructing complex structures and manipulating other creatures.
Includes bibliographical references and index.
Keywords: Birds -- Behavior